MPS 04-09 THE BENEFITS OF BISOPROLOL WERE COMPARABLE WITH CARVEDILOL. (September 2016) - Cho, Sang Cheol; Kim, Wan; Kang, Won Yu; Hwang, Sun Ho; Kim, Kyung Hwan; Ahn, Yeongkeun; Jeong, Myung Ho
Abstract : Objective: Although the benefits of carvedilol, non-cardioselective b-blocker, were demonstrated by several studies, there were no studies which evaluated the efficacy of bisoprolol, a class of b1-selective beta blocker, in secondary prevention of acute myocardial infarction (MI) patients who underwent percutaneous coronary intervention (PCI). Design and Method: Total 13, 813 patients who underwent PCI were treated with carvedilol or bisoprolol at discharge in Korean Acute MI Registry (KAMIR). After 1:2 propensity matching, 1, 806 patients were enrolled as bisoprolol group and 3, 612 patients as carvedilol group. The primary end point was composite of major adverse cardiac events (MACEs) which were defined as cardiac death, non-fatal MI, target vessel revascularization, and coronary artery bypass surgery. The secondary end point was defined as respective all-cause mortality, cardiac death, non-fatal MI, any revascularization or target vessel revascularization. Results: After adjustment of baseline characteristics by propensity matching, the MACEs free survival rate was not different between bisoprolol and carvedilol group. The subgroup analysis showed that cumulative incidence of MACEs was lower in bisoprolol group in patients having Killip class III or IV comparing with carvedilol group. The incidence of secondary end points was not different between two groups. Conclusions: The benefits of bisoprolol were comparable with carvedilol in secondary prevention of acute MI. The use of bisoprolol may be preferable in hemodynamically unstable acute MI patients on admission.